Algoplus performance to detect pain in depressed and/or demented old patients. (23rd February 2016) - Bonin‐Guillaume, S.; Jouve, E.; Lauretta, R.; Nalin, C.; Truillet, R.; Capriz, F.; Rat, P.
Abstract: Background: Algoplus detects acute pain in non‐verbal old patients (NVOP) with good psychometric properties. However, depression or dementia might modify the Algoplus score and/or item expression. Algoplus performances on demented and/or depressed old populations were tested. Methods: This multicentre cross‐sectional study included patients ≥65 years old with or without pain assigned to depression, dementia, depression & dementia or control groups. Each group was subjected to the Numerical Rating Scale (NRS) and behavioural scales (Algoplus, Doloplus). Depression and/or dementia status was rated and confirmed by blinded experts. Algoplus psychometric properties tested were: discriminant validity, convergent validity, item analysis, sensitivity to change after pain treatment and threshold determination. Results: The analysis included 171 patients (mean age 82.3 ± 6.3 years). Patients with and without pain in each group were comparable for age in all subgroups, except the older dementia subgroup. The mean Algoplus score was significantly higher for patients with than without pain, regardless of group assignment (Wilcoxon signed‐rank test, p  < 0.001). Algoplus and NRS or Doloplus had high convergent validity (respective Spearman correlation coefficients 0.79 and 0.87). The mean Algoplus score decreased significantly after starting pain management, regardless of group assignment. Some behaviours (i.e. "look") occurred more often in depressed patients, even those without pain. A threshold of 2 yielded respective sensitivity and specificity values of 95% and 96% for dementia patients, 62% and 79% for depressed patients, 96% and 71% for dementia & depressed patients, and 80% and 100% for controls. Conclusion: Algoplus accurately detected pain in depressed and/or dementia patients; and was sensitive to change after pain treatment. What does this study add?: Algoplus accurately detects pain in depressed and/or demented patients. A cut‐off score of 2 accurately detects the need for pain management in these populations. Algoplus is sensitive to change after treating pain.